PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI HOTEL SHANGRI-LA JAKARTA - Dian Lupitasari; Parlagutan Silitonga (LPPM Universitas Asa Indonesia, 2017)
Purpose- This research is meant to find out and to analyze the influence of compensation and work motivation to the performance of the employees. Design/methodology/approach- The data used is primary data obtained from questionnaires given 100 respondents drawn.The data analysis technique has been done by using multiple linear regression analysis and the hypothesis test has been done by using t test. Findings- The result of the test shows that the compensation has significant and positive influence to the performance of the employees, it has been proven by the positive coefficient regression value which is 0.648 and the significant value of t test is smaller than 0.05 which is 0.000. The motivation has significant and positive influence to the performance of the employees, it has been proven by the positive regression coefficient value which is 0.179 and the significance value of t test is smaller than 0.05 which is 0.016. Compensation and motivation simultaneously have a positive and significant effect on employee performance in strong category. This is due to the correlation coefficient of 0.610 with coefficient of determination of 37.21%.